A miniaturized printed UWB antenna with dual notching for X-b and and aeronautical radio navigation applications - Mohammad Ahmad Salamin; Sudipta Das; B. T. P. Madhav; Soufian Lakrit; Avisankar Roy; Asmaa Zugari (Universitas Ahmad Dahlan, 2020)
A low cost miniaturized UWB microstrip antenna with dual notched band for X band and aeronautical radio navigation (ARN) is presented in this article. The antenna (19 16Ã—